(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
The current research aims to (analyze the content of the questions of the sociological book for the third intermediate grade in the light of high-ranking thinking skills), to achieve this goal, the researcher prepared a list of high-ranking thinking skills, according to Al-Otoum’s classification of them and presented them to experts specialized in curricula and methods of teaching sociology, to extract virtual honesty, after that, the researcher proceeded to analyze the paragraphs of the book’s questions in the light of the skills contained in the list of final skills, then the researcher made sure of the stability of the analysis between his analysis and the analysis of an external analyst, the researcher reached the repetitions and percentages achieved by each of the high-ranking thinking skills, as contained in the questions of the systematic sociological textbook, based on these results, the researcher reached a set of conclusions, proposals and recommendations.